Evaluation of the Management of Patients with Detectable Viral Load after the Implementation of Routine Viral Load Monitoring in an Urban HIV Clinic in Uganda - Nsumba Steven Mark; Musomba Rachel; Arvind Kaimal; Mubiru Frank; Tibakabikoba Harriet; Lwanga Isaac; Mohammed Lamorde; Castelnuovo Barbara (AIDS Research and Treatment)
Objective. To describe the clinical decisions taken for patients failing on treatment and possible implementation leakages within the monitoring cascade at a large urban HIV Centre in Kampala, Uganda. Methods. As per internal clinic guidelines, VL results >1,000 copies/ml are flagged by a quality assurance officer and sent to the requesting clinician. The clinician fills a “decision form” choosing: (1) refer for adherence counselling, (2) repeat VL after 3 months, and (3) switch to second line. We performed data extraction on a random sample of 100 patients with VL test >1,000 copies/ml between January and August 2015. For each patient, we described the action taken by the clinicians. Results. Of 6,438 patients with VL performed, 1,021 (16%) had >1,000 copies/ml. Of the 100 (10.1%) clinical files sampled, 61% were female, median age was 39 years (IQR: 32–47), 81% were on 1st-line ART, 19% on 2nd-line, median CD4 count was 249 cells/µL (IQR: 145–390), median log10 VL 4.42 (IQR: 3.98–4.92). Doctors’ decisions were; refer for adherence counseling 49%, repeat VL for 25%, and switch to second line for 24% patients. Forty-one percent were not managed according to the guidelines. Of these, 29 (70.7%) were still active in care, 7 were tracked [5 (12.2%) lost to program, 2 (4.9%) dead] and 5 patients were not tracked. Conclusion. Despite the implementation of internal systems to manage patients failing ART, we found substantial leakages in the monitoring “cascade”. Additional measures and stronger clinical supervision are needed to make every test count, and to ensure appropriate management of patients failing on ART.